2023
DOI: 10.1002/ajb2.16261
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term biocrust responses to wildfires in Washington, USA

Heather T. Root,
Julian Chan,
Jeanne Ponzetti
et al.

Abstract: PremiseDryland ecosystems in the western United States are affected by invasive species, wildfires, livestock grazing, and climate change in ways that are difficult to distinguish. Biocrusts perform important ecological roles in these systems and are sensitive to all of these pressures.MethodsWe revisited a Washington, USA, site sampled for biocrusts in 1999 to focus on effects of exotic annual grass invasion and wildfires in the absence of livestock grazing. We examined changes between 1999 and 2020 using a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(133 reference statements)
0
0
0
Order By: Relevance
“…The role of biocrusts in hindering invasion by annual grass may increase in importance with anticipated changes in climate. A recent study conducted by Root et al (2023), found overall loses to biocrusts on paired sites with and without fire, although they were not able to account for compounding disturbances. We anticipate the response of biocrusts to fire found by Condon et al (2023) will be corroborated by future studies, in other regions, when researchers can account for compounding disturbances.…”
Section: Discussionmentioning
confidence: 86%
“…The role of biocrusts in hindering invasion by annual grass may increase in importance with anticipated changes in climate. A recent study conducted by Root et al (2023), found overall loses to biocrusts on paired sites with and without fire, although they were not able to account for compounding disturbances. We anticipate the response of biocrusts to fire found by Condon et al (2023) will be corroborated by future studies, in other regions, when researchers can account for compounding disturbances.…”
Section: Discussionmentioning
confidence: 86%